Bit-error rate performance of DVB-T2 signals over fading channels - Quan, Ya Jing (Nanyang Technological University, 2022)
DVB-T2 (Digital Video Broadcasting – Terrestrial 2) is the second version of the DVB-T standard. It uses Orthogonal Frequency Division Multiplexing (OFDM) modulation, concatenated channel coding, and interleaving to transport compressed digital audio, video, and other data in "physical layer pipes" (PLPs). This project aims to study on the bit-error rate performance of the DVB-T2 signals over Additive White Gaussian Noise (AWGN) and different types of fading channels, such as: Rayleigh fading channels and Rician fading channels.